2020
DOI: 10.3390/brainsci10120938
|View full text |Cite
|
Sign up to set email alerts
|

A Review and a Framework of Variables for Defining and Characterizing Tinnitus Subphenotypes

Abstract: Tinnitus patients can present with various characteristics, such as those related to the tinnitus perception, symptom severity, and pattern of comorbidities. It is speculated that this phenotypic heterogeneity is associated with differences in the underlying pathophysiology and personal reaction to the condition. However, there is as yet no established protocol for tinnitus profiling or subtyping, hindering progress in treatment development. This review summarizes data on variables that have been used in studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 93 publications
1
28
0
Order By: Relevance
“…They extracted 94 different variables which were processed in a framework of the most commonly used variables in subtyping. Tinnitus severity, hearing ability, age, and depressive symptoms were found to be the top four variables that were significant or important for classification 6 . However such characteristics can cover many domains such as demographic, audiological or psychological measures.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…They extracted 94 different variables which were processed in a framework of the most commonly used variables in subtyping. Tinnitus severity, hearing ability, age, and depressive symptoms were found to be the top four variables that were significant or important for classification 6 . However such characteristics can cover many domains such as demographic, audiological or psychological measures.…”
Section: Introductionmentioning
confidence: 97%
“…It is commonly believed that one of the explanations of the heterogeneity might be the existence of subtypes of tinnitus patients. Several attempts have been made to define these subtypes, but clinically usable types remain to be found 6 . In a recent review on tinnitus subtyping, the authors identified 64 articles that had reported on tinnitus subtyping 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the lack of an objective measure and the limited understanding of the mechanisms, research on tinnitus heterogeneity and tinnitus subtypes most often focuses on phenotypic heterogeneity of people with tinnitus; that is measurable traits that vary across individuals with tinnitus. These traits can include both general individual characteristics (not specific to people with tinnitus) such as demographics (e.g., gender) and co-existing conditions (e.g., hearing problems), and tinnitus-specific characteristics such as related to the tinnitus perception or its impact on the affected individual (Langguth et al, 2007;van den Berge et al, 2017;Genitsaridi et al, 2020;Van der Wal et al, 2020).…”
Section: Overviewmentioning
confidence: 99%
“…Regarding tinnitus management, while in younger adults, especially those presenting a normal standard audiometry, it is useful to have the evaluation of extended high frequency audiometry, usually this is not the case for those older than 65, according to our study results. These findings are important contributions for tinnitus subtyping, as in younger adults hearing loss in higher frequencies is likely to play a role in tinnitus pathophysiology, but this effect is probably reduced in older individuals [ 22 ]. Several studies have focused on the consequences of hearing on QoL, including in the older adult population with hearing loss [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%